(untitled) (Emergency Care Journal, 2018)
Proper pain management is an essential process when dealing with a patient suffering from blunt thoracic trauma, because it blocks the vicious circle that leads to the development of trauma related complications. This retrospective study deals with the use of pain killers administered in the Accidents and Emergency Department (ED) and prescribed at discharge to patients suffering from blunt thoracic trauma. The analysis confirms the existence of oligoanalgesia, that is an inadequate pain treatment, in clinical practice. Out of 214 patients involved in the study, only 78 patients (36.4%) received at least one pain killing drug during their stay in the ED. More than half of the patients discharged within 24 hours of admittance to the ED received no detailed advice about pain relief therapy and 8% of them (11 out of 136) returned to the ED within 15 days for persisting symptoms. Four were eventually admitted to hospital due to deterioration in their clinical conditions.